APPLICATION OF TECHNOLOGY IN ORGANIC FERTILIZER PROCESSING IN SAMBI VILLAGE, SRAGEN REGENCY - Prasetyo, Ari; Akbar, Hammar Ilham; Rovianto, Eki; Pramudi, Ganjar; Harsito, Catur; Muslim, Riyadi; Adika, Dimas (Abdi Masya, 2025)
The livestock waste in Sambi village has not been utilized for organic fertilizer. In fact, the number of livestock farmers is increasing every year, which has an impact on increasing waste. The purpose of this activity is to provide training and practice in making solid organic fertilizer from livestock waste in Sambi Village, Sambirejo District, Sragen Regency. Organic fertilizer is a form of fertilizer that comes from organic materials, such as animal waste, rotting plant residues, and other natural sources. Making organic fertilizer has the advantage of increasing community income and optimal use of organic fertilizer can improve soil fertility due to excessive use of chemical fertilizers. The majority of Sambi villagers have livestock and also cultivate agricultural crops. Waste has not been utilized for solid organic fertilizer and is still completely dependent on chemical fertilizers that cause physical damage to the soil, besides being expensive and rare. This program provides a package of solid organic fertilizer processing technology so that farmer groups can produce independently. In achieving the success of the program, socialization, training and mentoring have been carried out periodically. The production of organic fertilizer is expected to increase soil fertility and can be sold to increase community income